2016
DOI: 10.1039/c6ra09292f
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial mechanical properties of functionalized graphene–polymer nanocomposites

Abstract: The interfacial mechanical properties between graphene (GR) and a polymer matrix play a key role in load transfer capability for GR/polymer nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…Ding et al 11 found that the interfacial shear strength between graphene oxide and polymer was much stronger than that between Gr and polymer. Liu et al 12 showed that Gr graed with polymer chains could improve the shear strength while degrade the cohesive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al 11 found that the interfacial shear strength between graphene oxide and polymer was much stronger than that between Gr and polymer. Liu et al 12 showed that Gr graed with polymer chains could improve the shear strength while degrade the cohesive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Pull-Out Simulations. In order to comprehend interfacial dynamics and obtain mechanical properties of the interfacial region, pull-out simulations were performed through analogous methods suggested by several studies [23][24][25][26][27]. The x-direction lattice parameter of the amorphous cell was elongated to 75.5 Å , which is a summation of the graphene length (60 Å ) and van der Waals cut off distance (15.5 Å ), in order to remove the nonbonded interaction between successive cells along the x-direction [23,24].…”
Section: 3mentioning
confidence: 99%
“…The top and bottom regions of the graphene/epoxy system in the z-direction, marked by rounded rectangles in Fig. 3, were fixed [23,26,27]. At every step, the graphene was pulled out to 1.5-3 Å , and the cell went through energy minimization by the conjugate gradient method [23][24][25].…”
Section: 3mentioning
confidence: 99%
“…23,33,34 It is possible for a very strong interphase interaction to produce high stress transfer efficiency and to withstand large fracture loads, whereas a poor interface can lead to debonding of the interface and promote crack initiation. Various methods have been developed to introduce functional groups that can participate in the epoxy curing reaction to improve interfacial interactions through covalent bonds or noncovalent interactions.…”
Section: 17mentioning
confidence: 99%
“…22,23 In recent years, thermoplastic polymers in the forms of particles, lms, nanober veils, 19,24,25 or nanollers 5,[26][27][28] have been introduced as interleaves in the damage-prone interlaminar regions to improve interlaminar fracture toughness. Various effective mechanisms, such as ductile deformation, void formation and crazing, and bridging and pull-out have been identied as enhancing the energy absorption capability of the matrix and inhibiting generation and growth of cracks between layers.…”
Section: 17mentioning
confidence: 99%